THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR DEVELOPING THE SOCIO-PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS IN THE CONTEXT OF GLOBALIZATION - Karimov Ravshanbek Rizomatovich (Bright Mind Publishing, 2025)
This article explores the theoretical and methodological foundations for developing the socio-pedagogical competence of future teachers within the context of globalization. As modern societies undergo profound changes driven by technological innovation, cultural integration, and economic interdependence, the role of teachers is also evolving. The study emphasizes the need for teacher education programs to integrate global perspectives and foster the development of competencies that prepare educators to function effectively in diverse and dynamic environments. Socio-pedagogical competence is defined as a complex construct that includes social responsibility, intercultural communication, pedagogical ethics, and collaborative problem-solving skills. The article discusses the challenges of competence formation in higher pedagogical education and presents theoretical principles that underpin the design of educational models aimed at cultivating such qualities in future educators. It also proposes an integrative framework that combines cognitive, behavioral, and affective learning approaches for comprehensive competence development.
Keywords: Socio-pedagogical competence, teacher education, globalization, professional development, intercultural communication, higher pedagogical education, theoretical foundations.